Dialog antariman dalam Perspektif Fethullah Gülen - Khamami, Ahmad Rizqon (Religió: Jurnal Studi Agama-agama, 2012)
Samuel Huntington’s   Clash of Civilization reveals two civilization poles: Western and Eastern worlds. In the West perspective, Islam is a serious threat. Islam is regarded as a terrifying religion and having rigid characteristic, cruel, radical, no plurality mindset, terrorism, undeserved women subjected, dislike other groups, suicide bombing and others. Fethullah Gulen tried to change this view. He tries to combine Islamic values with universal humanism. The problem on how Islam could live in the modern world that aware of plurality is the background of Gulen’s concern. For him, the way to reconcile any matter of diversity’s problem is through dialogue. Dialogue in complex world’s society constitutes a delightful gift for answering society’s condition todays on. To create cosmopolitan Islam in the world, Gullen offers a kind of dialogues as a bargaining solution of an interreligious, culture and civilization problem. The endeavor of dialogue must be done through institutionalization of multi-cultural educational movement by establishing educational institution based on religious social harmony.